A Study of Behavior Problems in Children with Autism, Parenting Style and Need of Behaviors Management in Lower Northern Region - Pradujphongpetch, Jintana; Jaingam, Siriwimol; Triranaopas, Salakjit; Changpinit, Suwapatchara; Phoommisittiporn, Anucha (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The purpose of this study was to investigate behavior problems and parenting styles and parents’ needs dealing with behavioral problems in children with autism. The target of this study was a total number of 40 parents of children with autism, aged 3 – 8 years old, originally living in lower northern region. The tool used to collect data on this study was questionnaires and conducted a research on February 15th– 20th, 2022. Data in this study was analyzed with descriptive statistics: percentage, average, and standard deviation. The findings of the result indicated that the higher behavioral problems in children with autism were self – injury ( = 2.89, SD.= 0.48), second to hurting others and destroying property respectively ( = 2.29, SD. = 0.71 and =1.90, SD.= 1.06). The most of parenting styles in children with autism of lower northern region were permissive ( = 3.42, SD. = 0.64), second to authoritative and authoritarian respectively ( = 3.30, SD. = 0.32 and = 2.08, SD. = 0.56). The parents’ needs to handle with behavioral problems with autism children can be that firstly, continual monitoring and reporting how to be cooperative in handling with behavioral problems ( =4.65, SD. = 0.48), secondly, given suggestion by experts in coping with behavioral problems in real situations ( = 4.58, SD. = 0.55), and lastly, the progression of basic knowledge on the causes of behavioral problems with autism children ( = 3.80, SD. = 0.61).